# Solve for n -3/8n-11=4

-38n-11=4
Simplify each term.
Combine n and 38.
-n⋅38-11=4
Move 3 to the left of n.
-3n8-11=4
-3n8-11=4
Move all terms not containing n to the right side of the equation.
Add 11 to both sides of the equation.
-3n8=4+11
-3n8=15
-3n8=15
Multiply both sides of the equation by -83.
-83⋅(-3n8)=-83⋅15
Simplify both sides of the equation.
Simplify -83⋅(-3n8).
Cancel the common factor of 8.
Move the leading negative in -83 into the numerator.
-83⋅(-3n8)=-83⋅15
Move the leading negative in -3n8 into the numerator.
-83⋅-3n8=-83⋅15
Factor 8 out of -8.
8(-1)3⋅-3n8=-83⋅15
Cancel the common factor.
8⋅-13⋅-3n8=-83⋅15
Rewrite the expression.
-13⋅(-3n)=-83⋅15
-13⋅(-3n)=-83⋅15
Cancel the common factor of 3.
Factor 3 out of -3n.
-13⋅(3(-n))=-83⋅15
Cancel the common factor.
-13⋅(3(-n))=-83⋅15
Rewrite the expression.
-1⋅(-n)=-83⋅15
-1⋅(-n)=-83⋅15
Multiply.
Multiply -1 by -1.
1⋅n=-83⋅15
Multiply n by 1.
n=-83⋅15
n=-83⋅15
n=-83⋅15
Simplify -83⋅15.
Cancel the common factor of 3.
Move the leading negative in -83 into the numerator.
n=-83⋅15
Factor 3 out of 15.
n=-83⋅(3(5))
Cancel the common factor.
n=-83⋅(3⋅5)
Rewrite the expression.
n=-8⋅5
n=-8⋅5
Multiply -8 by 5.
n=-40
n=-40
n=-40
Solve for n -3/8n-11=4

### Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top